STRATEGI SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU - Shinta Ikrana Maharani; Chusnul Chotimah; Sulistyorini (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2023)
The main problem facing education today is the low quality of human resources and the inability of educational actors to keep up with the progress of science and technology in the era of globalization. Quality competition is something that is very urgent that must be met by schools, therefore what needs to be done is to improve the quality of human resources. The quality of human resources can be seen from the intellectual, spiritual, creativity, morality and responsibility aspects. Writing this article aims to find out the principal's strategy in improving teacher competence in terms of pedagogical, professional, personal and social competence. This article uses the literature study method. The results of the research show that the principal's strategy is to improve teacher competence through empowerment carried out by educational supervisors.